Factors affecting work-related non-fatal injuries among aged workers in South Korea - Park, Jungsun; Park, Jong-shik; Jung, Younghoon; Na, Minoh; Kim, Yangho (Frontiers in Public Health, 2024)
Introduction The objective of this paper is to investigate whether an aging workforce is associated with an increase in work-related non-fatal injuries and to explore the underlying reasons for this potential increase. Methods Aged workers were defined as those who were at least 55-years-old. Work-related non-fatal injuries were assessed in aged and young workers who were registered with the workers’ compensation system from 2017 to 2021 of South Korea. Results The mean estimated rate of work-related non-fatal injuries of aged workers (0.88/100) was about 2.5-times higher than that of younger workers (0.35/100). Most work-related non-fatal injuries in the older adults were in individuals working in the “construction sector” (36.0%), those with “elementary occupations (unskilled workers)” (45.0%), and those with employment status of “daily worker” (44.0%). “Trip & slip” (28.7%) and “falling” (19.6%) were more frequent types of work-related non-fatal injuries in aged workers relative to young workers. The category of “buildings, structures, and surfaces” was a more frequent cause of work-related non-fatal injuries in aged workers than young workers. Discussion The incidence of non-fatal work-related injuries is higher among aged workers compared to their younger counterparts. The increased occurrence of aged workers participating in precarious employment and jobs, along with the greater physical vulnerability, is likely the cause of their higher rate of work-related non-fatal injuries.